Mobilidade urbana: uma análise sociológica das ciclovias e ciclofaixas na cidade de São Paulo - Tarikian, Fabio Scaringella (2017)
Based on the analysis of the evolution of urban space and its main features throughout the historical and social development of the city of São Paulo, this dissertation presents a sociological analysis of the recent measures and policies to encourage the use of active transport, in particular the bicycle system, which has received a significant increase in recent years. Based on multidisciplinary tools, with special emphasis on the theory of 'Right to the City', we sought to deepen knowledge about the urban evolution model in the city of São Paulo, to correlate it with patterns of organization of mobility and transportation, considered as one of the main problems of the municipality today, in order to analyze its effects and consequences on social life in view of the mobilization around the appropriation or reconquest of the Urban Public Space